Insufficient Radiofrequency Ablation Promotes Hepatocellular Carcinoma Metastasis Through N6‐Methyladenosine mRNA Methylation‐Dependent Mechanism. Issue 3 (15th September 2021) - Su, Tianhong; Huang, Manling; Liao, Junbin; Lin, Shuibin; Yu, Peng; Yang, Jianhua; Cai, Yuhong; Zhu, Shenghua; Xu, Lixia; Peng, Zhenwei; Peng, Sui; Chen, Shuling; et al.
Abstract : Background and Aims: The dynamic N6‐methyladenosine (m 6 A) mRNA modification is essential for acute stress response and cancer progression. Sublethal heat stress from insufficient radiofrequency ablation (IRFA) has been confirmed to promote HCC progression; however, whether m 6 A machinery is involved in IRFA‐induced HCC recurrence remains open for study. Approach and Results: Using an IRFA HCC orthotopic mouse model, we detected a higher level of m 6 A reader YTH N6‐methyladenosine RNA binding protein 1‐3 (YTHDF1) in the sublethal‐heat–exposed transitional zone close to the ablation center than that in the farther area. In addition, we validated the increased m 6 A modification and elevated YTHDF1 protein level in sublethal‐heat–treated HCC cell lines, HCC patient‐derived xenograft (PDX) mouse model, and patients' HCC tissues. Functionally, gain‐of‐function/loss‐of‐function assays showed that YTHDF1 promotes HCC cell viability and metastasis. Knockdown of YTHDF1 drastically restrains the tumor metastasis evoked by sublethal heat treatment in tail vein injection lung metastasis and orthotopic HCC mouse models. Mechanistically, we found that sublethal heat treatment increases epidermal factor growth receptor (EGFR) m 6 A modification in the vicinity of the 5′ untranslated region and promotes its binding with YTHDF1, which enhances the translation of EGFR mRNA. The sublethal‐heat–induced up‐regulation of EGFR level was further confirmed in the IRFA HCC PDX mouse model and patients' tissues. Combination of YTHDF1 silencing and EGFR inhibition suppressed the malignancies of HCC cells synergically. Conclusions: The m 6 A‐YTHDF1‐EGFR axis promotes HCC progression after IRFA, supporting the rationale for targeting m 6 A machinery combined with EGFR inhibitors to suppress HCC metastasis after RFA.